Features of Combustion of Water-fuel Emulsions with Different Methods of Introducing Water into the Combustion Zone - Kolbasenko O.V.; Dymo B.V.; Anastasenko S.M.; Shostak O.V. (Problems of the Regional Energetics, 2025)
The main purpose of the article is to conduct research on combustion quality and determine nitrogen oxide concentrations for various methods of introducing water into the combustion chamber zone. To achieve the goal, the experimental study of combustion features was carried out on a combustion chamber model when supplying unwatered fuel oil of the M40 type, fuel oil, and water vapour in the amount equivalent to 30% of the mass of the fuel mixture, and two types of water-fuel emulsion with a water content of 15% and 30%. Values of gas temperature, concentration CO_2,H_2 та CH_4, as well as nitrogen oxides and (NO_2:NO) ratio were measured along the length of the combustion chamber. Studies have shown a reduction in nitrogen oxide emissions and an increase in the (NO_2:NO) ratio to 0,330 when supplying a water-fuel emulsion with a water content of up to 30%. This increases absorption properties of sulfuric acid in flue gases and reduces the intensity of low-temperature corrosion. When using a water-fuel emulsion of such a composition, it becomes possible to use condensation surfaces of boilers with a significant increase in their efficiency of up to 5…9% Experimental studies have also shown that additional generation Н_2, significant thermal decomposition effect NO_x NO_x, generation of acoustic vibrations and microexplosions take place. This indicates that water-fuel emulsions are a special type of fuel, qualitatively and quantitatively changing the physicochemical processes of combustion. The most important results, constituting the significance of the research, are the experimental proofs of the advantage of using an innovative technology for preparing water-fuel emulsion, based on intense cavitation treatment of the fuel mixed with water obtained from an electrodialysis unit. This achieves better emulsion combustion performance compared to other methods of its preparation and the introduction of water into the combustion zone.